Memperkuat Karakter Profil Pelajar Pancasila melalui Program Pengolahan Sampah Plastik di SMP Negeri 1 Tembuku - Trikusuma, Ayu Swandewi (Metta : Jurnal Ilmu Multidisiplin, 2022)
Garbage is one of problem that often arises at the moment. It is not only in our country, however it has also become a world problem. Considering that there is still a lack of public awareness regarding concern for the surrounding environment which results in environmental damage and natural disasters. The various natural phenomena that occur in Indonesia certainly underlie the importance of character education for all Indonesian society. This research reveals the importance of instilling character education in students at every level through a plastic waste processing program. The plastic waste processing program is a form of character development for the Profil Pelajar Pancasila to be able to strengthen the character of the Profil Pelajar Pancasila, especially for the dimensions of religious, devotion to God and good character, mutual cooperation, independence and creativity, which is related to an attitude of caring for the environment. This research was carried out with the aim of finding out that innovation programs carried out by schools can act as effective media to strengthen the expected character of the Profil Pelajar Pancasila. This research was qualitative approach with descriptive research type. Data was obtained through literature study which was collected by browsing articles, reading literature books, and analyzing research results. The research results show that the plastic waste processing program carried out routinely in schools is able to provide a breath of fresh air in the world of education, especially in instilling environmentally caring character education in students. It is hoped that all school will participate in efforts for students' independence in managing waste in their community. Instilling the character of caring for the environment from an early age is very important, it makes students have awareness and concern for their environment.